A case of Tocilizumab-induced thrombocytopenia in steroid-resistant Graves orbitopathy. (27th January 2023) - Cuculescu, Victoria; Vudu, Stela; Rizov, Cristina; Vudu, Lorina
Abstract: Introduction: Graves' orbitopathy (GO) is the main extrathyroidal manifestation of Graves' disease (GD). It is more common in women, but men have more severe evolution of the disease. GO appears in 25–70% of patients with GD and can have a severe evolution in 5% cases and even lead to sight loss. In mild forms local treatment is often sufficient to alleviate eye symptoms. However, in moderate-to-severe cases systemic glucocorticoids are used, combined or not with immunosuppressive drugs. In moderate-to-severe glucocorticoid-refractory cases, conventional and biological immunosuppressive drugs have been used, among which is treatment with Tocilizumab (TCZ) – a monoclonal antibody targeting the interleukin-6 receptor, involved in GO's pathogenesis. Clinical Case: A 49 years old former smoking Caucasian man was admitted to the endocrinology unit with asymmetrical bilateral exophthalmos, spontaneous and movement induced retrobulbar pain, hyperlacrimation. He has been diagnosed with Graves disease 9 months prior to the admission to our clinic. At that time the patient was treated with antithyroid drugs and oral prednisolone. The clinical activity score – CAS 7/7 points confirmed an active form of GO. Laboratory findings revealed a suppressed TSH 0.01 UI/ml, increased freeT4 40, 1 pmol/l, positive TR-Ab (30, 04 IU/L). Treatment with high-dose regimen of i.v. methylprednisolone (Mt), cumulative dose 5.75 g in 12 weeks was applied. The patient was soon thereafter admitted repeatedly for evaluation: a non-response to Mt has been established, occurrence of diplopia, convergent strabismus, therefore a second-line treatment with tocilizumab (TCZ) was considered. His blood platelet count before TCZ was 158×10*9. The patient received the first 8 mg/kg dose of i.v. TCZ and showed an improvement in the CAS score (5/7 points), however 1 month later, the platelet count had decreased to 48×10*3 and further treatment with TCZ has been postponed until thrombocyte count increases above 100×10*9. His oral medicines were thiamazole and levothyroxine. Other causes of thrombocytopenia (HIV, Hepatitis C, Ebstein-Barr virus, Helicobacter pylori, liver disease) have been excluded. 7 weeks later thrombocyte count increased spontaneously to 102×10*3 and TCZ treatment has been resumed. Discussion. The mechanism of thrombocytopenia induced by TCZ is dependent on its effect on IL-6 receptor, which stimulates thrombopoiesis through thrombopoietin induction. Clinical studies prove the effectiveness of TCZ in the treatment of GO, but side effects limit its use. Older age and low platelet count before TCZ treatment were associated with the development of thrombocytopenia after treatment. Conclusion: Thrombocytopenia induced by tocilizumab is tolerable. However, in patients with known risk factors, close monitoring of platelet counts is recommended. An individual approach is appropriate, considering the high cost of the drug, side effects and comorbidities.